2018
DOI: 10.1038/s41598-018-35320-8
|View full text |Cite
|
Sign up to set email alerts
|

A standardized herbal extract PM014 ameliorates pulmonary fibrosis by suppressing the TGF-β1 pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating and common chronic lung disease pathologically characterized by loss of epithelial cells and activation of fibroblasts and myofibroblasts. The etiology of IPF remains unclear and the disease pathology is poorly understood with no known efficacious therapy. PM014 is an herbal extract that has been shown to have beneficial effects in pulmonary diseases, which are likely to exert anti-inflammatory bioactions. In the present study, we observed that bleomycin (BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…In vitro and in vivo results from other studies shows a similar effect of PM014 in murine models of chronic obstructive pulmonary disease (COPD) [4,5] and cockroach allergen-induced asthma [6]. In addition, PM014 has recently been shown to improve pulmonary fibrosis induced by bleomycin [7]. Furthermore, a thirteen-week study of PM014 showed no subchronic oral toxicity in animal model, providing supportive evidence of the safety of PM014.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…In vitro and in vivo results from other studies shows a similar effect of PM014 in murine models of chronic obstructive pulmonary disease (COPD) [4,5] and cockroach allergen-induced asthma [6]. In addition, PM014 has recently been shown to improve pulmonary fibrosis induced by bleomycin [7]. Furthermore, a thirteen-week study of PM014 showed no subchronic oral toxicity in animal model, providing supportive evidence of the safety of PM014.…”
mentioning
confidence: 62%
“…The components of PM014 were purchased from Kyung Hee Herb Pharm (Seoul, South Korea) and prepared by Hanlim Pharm Co. LTD (Yongin, Korea) as described in a previous studies [3,7]. The preparation of the medicinal herbs was based on the standards provided by The Korean Herbal Pharmacopoeia published by the Korean Food and Drugs Administration (KFDA).…”
Section: Preparation Of Pm014mentioning
confidence: 99%
See 3 more Smart Citations